(G,P)-opers and global Slodowy slices - Collier, Brian; Sanders, Andrew (Advances in mathematics, 2021)
In this paper, we introduce a generalization of G-opers for arbitrary parabolic subgroups P<G of a complex semisimple Lie group. For parabolic subgroups associated to “even nilpotents”, we parameterize (G,P)-opers by an object generalizing the base of the Hitchin fibration. In particular, we describe and parameterize families of opers associated to higher Teichmüller spaces.
Available online 9 November 2020
Gesehen am 17.02.2022